THE EFFECTIVENESS OF NUMBER HEAD TOGETHER (NHT) IN TEACHING READING COMPREHENSION AT TENTH GRADE STUDENTS OF MAN 4 KEDIRI - Hariyati, Hariyati; Setyawati, Lely (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2021)
The aim of research is to know the effectiveness of Number Head Together (NHT) in Teaching Reading Comprehension at tenth grade students of MAN 4 Kediri. Quantitative post-test only control group design used the approach to design this research. The subject of the research is tenth grade student of MAN 4 Kediri. The subject were X MIA 1 class as experimental class which consist of 36 students and X MIA 2 class as control class which consist of 36 students. To get data, the researcher use test. The data analyzed by using t- test can be found with SPSS 16.0. The mean score of students’ reading comprehension in experimental class belongs to very good category. Its score 83.19. Meanwhile, the mean score in control class belongs to good category with mean score 77.22. The result of statistical computation value of the independent sample t-test is 3.050 with t table within degree of freedom (df) 70 at 5% significant level is 2.647. It can be seen that t-statistic value is higher than t-table. Because there is significant increase in student’s reading comprehension after doing treatment, it can be said that number head together in reading comprehension of the tenth grade students of MAN 4 Kediri in academic year 2018/2019 is effective. So the alternative hypothesis was accepted.